Babycakes - Kauffman, Donna (Kauffman, Donna. Cupcake Club romance., 2012)
"Kit Bellamy was raised on pie. Mamie Sue's "Peanut Pies", to be exact, the family company her scheming brother-in-law sold out from under her. Now Kit needs a new recipe for her life-and sleepy Sugarberry Island is the first ingredient. Running mail-order cupcake business Babycakes is a chance to get her baking on again-until she meets tall, dark, and adorable lawyer Morgan Westlake. New to the island to raise his goddaughter, he's as mouth-watering as any of Kit's creations. It's just her luck that he's the spawn of the very law firm that helped crush her dreams...Fortunately, Kit's new friends can assure her that Morgan is no typical Westlake-and that even lawyers, not to mention single dads, need romance. If Kit can just be persuaded to follow her appetite-and set another place at her holiday table-her sweetest dreams just might come true..."--P. [4] of cover.